2019
DOI: 10.1007/s11769-019-1063-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Dynamics of Grassland Net Primary Productivity in Response to Climate Change at the Global Scale

Abstract: Understanding the net primary productivity (NPP) of grassland is crucial to evaluate the terrestrial carbon cycle. In this study, we investigated the spatial distribution and the area of global grassland across the globe. Then, we used the Carnegie-Ames-Stanford Approach (CASA) model to estimate global grassland NPP and explore the spatio-temporal variations of grassland NPP in response to climate change from 1982 to 2008. Results showed that the largest area of grassland distribution during the study period w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…In addition, the NPP of temperate meadow had a significantly positive relationship with precipitation in summer, confirming that moisture is the key limiting factor for vegetation growth in the arid temperate grassland region. Therefore, increased summer maximum temperature can adversely affect grasslands by increasing evaporation ( Liu et al, 2019 ). The negative correlation between grassland NPP and summer maximum temperature confirms our second hypothesis that the increase of daytime temperature may reduce the grassland NPP in warm season.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the NPP of temperate meadow had a significantly positive relationship with precipitation in summer, confirming that moisture is the key limiting factor for vegetation growth in the arid temperate grassland region. Therefore, increased summer maximum temperature can adversely affect grasslands by increasing evaporation ( Liu et al, 2019 ). The negative correlation between grassland NPP and summer maximum temperature confirms our second hypothesis that the increase of daytime temperature may reduce the grassland NPP in warm season.…”
Section: Discussionmentioning
confidence: 99%
“…Although climate change has until now had relatively minor impacts on degradation, it is expected to become more important for degradation in the future (3, 4), exacerbating the effects of land-use change. Analyses of remotely sensed vegetation greenness (and vegetation browning) as well as model-based studies found that climate change has contributed to degradation chiefly in regions located around 15-45 o S, although studies disagree regarding the exact region of impact (36,60,61). Model-based estimates of NPP indicate that climate change is an important driver of degradation in approximately 35-45% of the world's degraded grasslands (36,61).…”
Section: Direct and Indirect Impacts Of Climate Changementioning
confidence: 99%
“…Analyses of remotely sensed vegetation greenness (and vegetation browning) as well as model-based studies found that climate change has contributed to degradation chiefly in regions located around 15-45 o S, although studies disagree regarding the exact region of impact (36,60,61). Model-based estimates of NPP indicate that climate change is an important driver of degradation in approximately 35-45% of the world's degraded grasslands (36,61). Attribution of climate change as a driver of degradation is made more difficult by concurrent increases in atmospheric CO 2 and the large regional variability in observed and projected climate trends.…”
Section: Direct and Indirect Impacts Of Climate Changementioning
confidence: 99%
“…Global climate change has an extremely significant impact on surface vegetation cover. At the same time, the changing characteristics of surface vegetation cover will have corresponding feedback on regional climate and global climate systems [1][2][3][4]. As a key component of the terrestrial ecosystem [5,6], grassland is one of the most common vegetation types, providing various ecosystem and social service functions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%